2021
DOI: 10.1021/acs.jnatprod.0c00807
|View full text |Cite
|
Sign up to set email alerts
|

Planomonospora: A Metabolomics Perspective on an Underexplored Actinobacteria Genus

Abstract: Despite an excellent track record, microbial drug discovery suffers from high rates of rediscovery. Better workflows for the rapid investigation of complex extracts are needed to increase throughput and to allow early prioritization of samples. In addition, systematic characterization of poorly explored strains is seldomly performed. Here, we report a metabolomic study of 72 isolates belonging to the rare actinomycete genus Planomonospora , using a workflow of commonly used open access t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…Targeted linking and automated approaches for accelerating drug discovery have been reviewed [39,53]. Recently, metabolomic and genomic data of 72 isolates belonging to the rare actinomycete genus Planomonospora were analysed using publicly available tools to link specialised metabolites to their corresponding BGCs [77]. The authors were able to manually pair siomycin congeners to a RiPP BGC and a new salinichelin-like metabolite to the known BGC encoding for erythrochelin.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted linking and automated approaches for accelerating drug discovery have been reviewed [39,53]. Recently, metabolomic and genomic data of 72 isolates belonging to the rare actinomycete genus Planomonospora were analysed using publicly available tools to link specialised metabolites to their corresponding BGCs [77]. The authors were able to manually pair siomycin congeners to a RiPP BGC and a new salinichelin-like metabolite to the known BGC encoding for erythrochelin.…”
Section: Discussionmentioning
confidence: 99%
“…Stemming from metabolomic studies of Planomonospora strains from Naicons' strain collection [101], Zdouc et al purified and elucidated the structure of a novel tripeptide with an unusual carbon-carbon (C-C) bond between amino acids. The authors propose to call this novel class of compounds biarylitides, since the products feature a C-C bridge between the aromatic amino acid residues.…”
Section: A Biaryl-linked Tripeptide From Planomonospora Reveals a Widespread Class Of Minimal Ripp Gene Clusters [93]mentioning
confidence: 99%
“…6,7 Particularly promising is the combination of metabolomic tools to poorly explored bacterial taxa. In recent work on bacterial strains belonging to the actinobacterial genus Planomonospora, we uncovered novel chemistry, which led to a family of unexpected biosynthetic gene clusters (BGCs), 8,9 which in turn helped uncover further novel chemistry. 10 We previously reported that strains belonging to another actinobacterial genus, Actinoallomurus, produce at high frequency molecules with antibacterial activity, 11 with several new variants of known scaffolds identified through bioactivity-based screening.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Particularly promising is the combination of metabolomic tools to poorly explored bacterial taxa. In recent work on bacterial strains belonging to the actinobacterial genus Planomonospora , we uncovered novel chemistry, which led to a family of unexpected biosynthetic gene clusters (BGCs), 8,9 which in turn helped uncover further novel chemistry. 10…”
Section: Introductionmentioning
confidence: 99%